A decentralised-control protocol for Source Specific Multicast. (11th August 2006) - Al-Begain, Khalid; Cao, Yewen
A novel Source Specific Multicast (SSM) protocol, called Scalable Recursive Multicast (SREM) is proposed. Unlike existing SSM protocols, which in general use the source-centralised control mechanism, SREM is a decentralised-control multicast scheme. A pair of Branch Node Messages (BNMs) is introduced to construct a branching node-based multicast tree, which is built up gradually, locally and dynamically as group members join/leave. Delivering multicast packets is carried out recursively between BN Routers by unicast. SREM has fixed size control messages, and low join/leave latency and is scalable. Simulation shows that SREM outperforms recently proposed algorithms in terms of processing and delivering costs.